The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-34565-7
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing of Candida albicans isolates from the oral cavities of patients undergoing haemodialysis

Abstract: This study evaluates the prevalence, diversity, and genetic profiles of Candida albicans isolates recovered from the oral cavities of haemodialysis patients. Oral swab samples were obtained from haemodialysis patients (n = 126) and healthy control subjects (n = 233) and Candida species were characterised. There was no significant difference between the haemodialysis and control groups in the prevalence of yeast carriers (23.6% vs. 31.0%, respectively) or C. albicans carriers (19.8% vs. 21.0%, respectively). C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 68 publications
0
12
2
Order By: Relevance
“…Of note, 4 of the 6 new DSTs were recovered from human patients, whereas the majority of animal isolates belonged to previously described MLST genotypes (19/24; 79%) (Table 1 ). In order to reveal the phylogenetic relationship between isolates, we performed cluster analysis of isolates included in the present study and two reference DSTs from each previously assigned clades determined by UPGMA analysis [ 10 ]. The 30 C. albicans isolates grouped into 8 clades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, 4 of the 6 new DSTs were recovered from human patients, whereas the majority of animal isolates belonged to previously described MLST genotypes (19/24; 79%) (Table 1 ). In order to reveal the phylogenetic relationship between isolates, we performed cluster analysis of isolates included in the present study and two reference DSTs from each previously assigned clades determined by UPGMA analysis [ 10 ]. The 30 C. albicans isolates grouped into 8 clades.…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping strains within a microbial species on the basis of DNA sequences at multiple loci has greatly advanced study of the epidemiology and evolutionary phylogenetic of many fungal pathogens including C. albicans [ 5 8 ]. At the population level, molecular typing has revealed 19 clades of C. albicans strains so far [ 9 , 10 ]. Some of these clades seem to exhibit geographical enrichment or phenotype specificities, however, no correlation between clade assignment and the ability of strains to cause different forms of infection or host specificity has been established yet [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bootstrap values of ≥75% were defined as statistically significant. Finally, clade numbers were assigned according to previous publications (Odds et al, 2007; Tsai et al, 2015; Wu et al, 2015; Gong et al, 2018) or by using the eBURST method as described previously (Odds et al, 2007). DSTs from clade numbers that were not presented in our strains were also included as reference DSTs for UPGMA and NJ analysis (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) has been widely used to study the molecular characterization of C. albicans based on the sequences of seven housekeeping genes ( AAT1a , ACC1 , ADP1 , MPI1b , SYA1 , VPS13 , and ZWF1b ) (Bougnoux et al, 2003; Afsarian et al, 2015). This method has identified 19 clades worldwide (Shin et al, 2011; Gong et al, 2018). A 2007 global study of 1,391 C. albicans strains showed that clade 1 was the most common (33.6%) (Odds et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] This method has identified 19 clades plus singletons worldwide. 13,14 In this study, we used molecular techniques and cluster analysis to analyse the distribution of infected agents across China.…”
Section: Introductionmentioning
confidence: 99%